Effects of smoking on oral health: Awareness among dental patients and their attitude towards its cessation - Archana B More; Anisha Rodrigues; Bhakti J Sadhu (Wolters Kluwer Medknow Publications, 2021)
Context: Tobacco smoking is the leading cause of preventable premature mortality in the world. Smoking is also detrimental to oral health, causing unaesthetic tooth staining, bad breath, periodontal diseases, impaired healing of wounds, increased risk of dental implant failure, precancerous conditions and oral cancer. Aims: To assess the awareness of the effects of smoking on oral health among smokers in Mangalore city and to assess the smoker's willingness to quit smoking. Settings and Design: Cross-sectional study. Material and Methods: Data was collected from 140 participants. A cross sectional study was conducted using a self-administered questionnaire to determine the sociodemographic characteristics, awareness about the effects of smoking on oral health and their willingness to participate in smoking cessation programs and to quit smoking. Results: There was statistically significant difference found in the level of awareness of the smoking effects on oral cancer, on tooth staining and dental implants. However, it was observed that the upper socioeconomic class showed a comparatively higher level of awareness than the other classes. No significant differences were found in the level of awareness of the smoking effects on gum disease and on wound healing. One hundred and thirteen individual out of 140 expressed their willingness to quit smoking and also 78 respondents showed a positive attitude toward participation in cessation programs.Conclusion: Participants in this sample had some knowledge about the effects of smoking, but were not much aware of its effect on dental implants, requiring further education.